2009
DOI: 10.1097/wnp.0b013e3181c2bcf7
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory-Related-Evoked Potential Measures of Respiratory Sensory Gating in Attend and Ignore Conditions

Abstract: Respiratory sensory gating is evidenced by decreased respiratory-related-evoked potentials (RREP) amplitude of the N1 peak for the second stimulus (S2) when two occlusions are separated by a 500-millisecond interval. The RREP N1 peak amplitude ratio of the S2 and the first occlusion (S1), S2/S1, is usually <0.5. Controlled attention of respiratory loads is measured by the P300 peak of the RREP. We hypothesized that the paired occlusion elicited N1 and the P300 peak amplitudes will be modulated by controlled at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
12
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 41 publications
3
12
0
Order By: Relevance
“…Our results of the prolonged P3 latency and reduced P3 amplitude in the GAD group, compared to the healthy controls, are consistent with some notions given by the earlier RREP studies examining the effect of attention (Chan and Davenport, 2009;Harver et al, 1995;von Leupoldt et al, 2010bvon Leupoldt et al, , 2011aWebster and Colrain, 2000). In general, it has been suggested that P3 peak latency and amplitudes may be related to information processing speed and attentional resources allocation, respectively (Harver et al, 1995;Webster and Colrain, 2000).…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Our results of the prolonged P3 latency and reduced P3 amplitude in the GAD group, compared to the healthy controls, are consistent with some notions given by the earlier RREP studies examining the effect of attention (Chan and Davenport, 2009;Harver et al, 1995;von Leupoldt et al, 2010bvon Leupoldt et al, , 2011aWebster and Colrain, 2000). In general, it has been suggested that P3 peak latency and amplitudes may be related to information processing speed and attentional resources allocation, respectively (Harver et al, 1995;Webster and Colrain, 2000).…”
Section: Discussionsupporting
confidence: 94%
“…Moreover, Chan and Davenport (2009) found that, in a gating paradigm, the P3 amplitudes of the first stimulus are increased significantly and therefore enhance the gating function by "filtering" in, or reallocating more necessary information related to the first stimulus for performing the attend task (Chan and Davenport, 2009). Although the current study does not have behavioral data such as reported number of occlusions counted to compare with the finding of longer latency and reduced amplitude of the P3 in the GAD group, it is reasoned that this delayed P3 could be due to slower information processing speed related to working memory which has long been reported in the literature about GAD (Rozenman et al, 2014).…”
Section: Discussionmentioning
confidence: 97%
“…Indeed, their amplitudes correlate with the stimulus magnitude (Davenport et al, 2007;Davenport, 1997, 1999) but not with attention (Chan and Davenport, 2009;Webster and Colrain, 2000b) nor with emotion (von Leupoldt et al, 2011Leupoldt et al, , 2010b, consistent with the present study. This suggests that the peripheral encoding of sensory signals and the initial cortical activations are not affected by emotion.…”
Section: Effect Of Unpleasant Emotions On Rrep Componentssupporting
confidence: 92%
“…(2011) established in young healthy adults that there is cortical processing of pharyngeal mechanical stimulation, termed oropharyngeal sensory evoked potential (PSEP). Additionally, this technique can evaluate whether the processing of the information changes during a paired stimulus paradigm (500 ms interval), termed sensory gating (Chan and Davenport, 2009, 2010; Chan and Davenport, 2008; Wheeler-Hegland et al, 2010). …”
Section: Introductionmentioning
confidence: 99%
“…Wheeler-Hegland (2010) provided evidence of limited gating of the PSEP in young healthy adults, and more specifically that central processing of mechanical stimulation to the pharyngeal wall is different than other somatosensory modalities i.e. respiratory-related (Chan and Davenport, 2009; Chan and Davenport, 2008) and auditory (Korzyukov et al, 2007) which have significant suppression of the second stimulus event. We hypothesize that limited gating of pharyngeal mechanical stimulation is advantageous for effective airway protection, due to the time-course of the pharyngeal phase of swallow and the ability of humans to perform sequential swallow tasks.…”
Section: Introductionmentioning
confidence: 99%